1999
DOI: 10.1079/095442299108728956
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional ergogenic aids and exercise performance

Abstract: The use of nutritional supplements in sport is widespread and few serious athletes do not, at some stage in their career, succumb to the temptation to experiment with one or more nutritional supplements. Nutritional ergogenic aids are aimed primarily at enhancing performance (either by affecting energy metabolism or by an effect on the central nervous system), at increasing lean body mass or muscle mass by stimulation of protein synthesis and at reducing body fat content. Although not strictly ergogenic (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1
16

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 107 publications
(114 reference statements)
0
53
1
16
Order By: Relevance
“…All participants habitually ingested caffeine although none were heavy caffeine users (mean ± SD of caffeine consumption = 149.2 ± 58 mg/day, range = 90-210 mg/day). Caffeine intake was established using a 24 hour recall questionnaire (25). All participants completed a health history questionnaire to ensure that they met all inclusion criteria.…”
Section: Participantsmentioning
confidence: 99%
“…All participants habitually ingested caffeine although none were heavy caffeine users (mean ± SD of caffeine consumption = 149.2 ± 58 mg/day, range = 90-210 mg/day). Caffeine intake was established using a 24 hour recall questionnaire (25). All participants completed a health history questionnaire to ensure that they met all inclusion criteria.…”
Section: Participantsmentioning
confidence: 99%
“…A wide range of experimental models and subject groups have been employed, and it is difficult to determine consistent patterns that could account for the effects seen in some studies but not in others. There is strong support for effects on repeated sprints, with less conclusive evidence for effects on single sprints and on muscle strength (Maughan, 1999;Williams et al 1999). Many studies and much anecdotal information support the suggestion that acute supplementation with creatine is associated with a prompt gain in body mass.…”
Section: Creatinementioning
confidence: 99%
“…A few supplements have been the subject of closer scrutiny, and there is evidence to support the use of creatine, caffeine, bicarbonate and perhaps also a small number of other compounds. Comprehensive reviews can be found elsewhere (Maughan, 1999(Maughan, , 2000a, and only a few individual supplements will be considered here.…”
Section: Dietary Supplements and Ergogenic Aidsmentioning
confidence: 99%
“…Participants that completed the study habitually consumed caffeine, but were not heavy caffeine users (125 ± 95 mg/day). Caffeine intake was measured using a 24 hour recall questionnaire (Maughan 1999). …”
Section: Participantsmentioning
confidence: 99%